Project-Based Learning for Critical Thinking in Young English Learners Class (A Study at Eighth Grade Students of SMPN 11 Bengkulu Tengah) - Vera Puspita Sari; Fera Zasrianita; Andriadi Andriadi (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study investigates the effect of Project-Based Learning (PjBL) on the development of critical thinking skills among eighth-grade students in English as a Foreign Language (EFL) classes at SMPN 11 Bengkulu Tengah. Employing a quantitative research design, the study collected data from 21 students in class VIII A using a structured questionnaire consisting of 30 items on a four-point Likert scale. Descriptive statistical analysis was applied to examine students’ perceptions across five indicators: understanding of PjBL, project engagement, motivation, collaboration and communication, and critical thinking skills. The findings reveal that the majority of students responded positively to the implementation of PjBL, demonstrating notable improvement in critical thinking indicators such as identifying problems (90%), using evidence-based reasoning (90%), reflecting before answering (95%), evaluating work results (90%), and recognizing the importance of critical thinking (100%). In addition to cognitive gains, PjBL enhanced students’ collaboration, communication, and confidence, with 90% reporting active participation in discussions and increased motivation. These results suggest that PjBL fosters an interactive, contextual, and learner-centered environment that supports the development of 21st-century skills, particularly critical thinking. The study concludes that PjBL can be an effective instructional strategy for junior high school EFL contexts, although further research employing pre-/post-tests and qualitative methods is recommended to complement these findings.